Seismic Performance of Offshore Piers under Wave Impact and Chloride Ion Corrosion Environment - Yin Gu; Anhua Yu; Xiaolong Zhang (Shock and Vibration)
Offshore bridges may suffer from chloride ion corrosion, tsunami wave impact, and earthquake. However, the coupling effects of multiple factors have not been fully considered. This paper studied multiple degradation effects on the seismic performance of offshore piers considering tsunami wave impact, chloride ion corrosion, and their interaction. Firstly, through the scale model test of tsunami wave flume, the wave force of box girder structures and piers under different tsunami wave conditions is measured. Then, according to the corrosion characteristics of coastal chloride salts on reinforced concrete bridge piers, the corrosion parameters is selected by Latin hypercube sampling, and the influence of corrosion expansion and cracking of bridge pier cover on the chloride ion corrosion process is considered to modify the degradation model of corroded reinforced concrete materials. Finally, the wave load measured by the test is converted by the similarity criterion of the fluid mechanic test and loaded into the ABAQUS full-bridge model, and the pier after the tsunami wave is evaluated by the pushover analysis. The bearing capacity and lateral stiffness of the corroded pier before and after different tsunami waves are compared. The results show that the lateral bearing capacity and stiffness of bridge piers are, respectively, decreased by 27.6% and 6.2% after 30 years of service. Without corrosion, the lateral bearing capacity and stiffness of piers were, respectively, reduced by 11.45% and 10.6% after HXB-5 wave impact. After 30 years of service, the lateral bearing capacity and stiffness of bridge piers are, respectively, reduced by 41.8% and 22.5% under the combined action of corrosion and HXB-5 wave impact. It is found that the coupling effects of multiple degradation factors were more significant than the simple superposition ones. Therefore, the coupling effect of multiple factors should be considered in practical engineering.